2017
DOI: 10.4187/respcare.05751
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Sedation in Subjects With ARDS Undergoing Continuous Lateral Rotational Therapy

Abstract: This study supports the feasibility of isoflurane sedation using continuous lateral rotational therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Also, the opioid dose was significantly lower on isoflurane compared to propofol days. A reduced opioid dose may facilitate spontaneous breathing [37,38] and promote intestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the opioid dose was significantly lower on isoflurane compared to propofol days. A reduced opioid dose may facilitate spontaneous breathing [37,38] and promote intestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…Whether spontaneous respiration in ARDS is helpful or harmful remains an area of debate [8]. Clinical studies confirmed that sedation inhibits the driving of the respiratory center and reduces the amplitude of spontaneous respiration, especially for early moderate to severe ARDS, deep sedation and even muscle relaxation can greatly improve the prognosis of patients and reduce the incidence of VILI [9,10]. However, for mild ARDS or convalescent ARDS, it is recommended to keep spontaneous respiration, which may be more conducive to the recovery of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The prerequisite for using the Anaesthetic Conserving Device (ACD) AnaConDa ® (Sedana Medical AB, Danderyd, Sweden) or the MIRUS TM system (TIM, Koblenz, Germany) depends on several clinical parameters (see Figure 1 ). If lung compliance is acceptable, and CO 2 can be reduced sufficiently, both types of systems are able to maintain spontaneous breathing[ 19 - 21 ]. However, if lung compliance is poor, reduction of dead space and active humidification is necessary, which can be facilitated by inhaled sedation via a circle breathing system[ 22 , 23 ].…”
Section: Administration Of Volatile Anesthetics During Ards Therapymentioning
confidence: 99%